Efficacy of a Comprehensive Early Childhood Curriculum to Enhance Children's Success. (May 2019) - Odom, Samuel L.; Butera, Gretchen; Diamond, Karen E.; Hanson, Marci J.; Horn, Eva; Lieber, Joan; Palmer, Susan; Fleming, Kandace; Marquis, Janet
The purpose of this study was to examine the efficacy of the Children's School Success (CSS) curriculum for 4-year-old children enrolled in preschool programs designed to prepare them for success in their early public school grades. The study took place in preschool classes located in five regionally distributed states, all of which were inclusive of children with disabilities as well as other learning needs. Participants were 1, 117 children from three subgroups (i.e., children living in poverty, children who were English Learners, and children with identified disabilities). Effects were also examined for children from these groups who had challenging behavior. Positive effects on different measures of vocabulary, letter knowledge, math, and social problem solving were found for children who were at risk due to poverty only and children who were English Learners. There was a consistent finding of "non-effects" for the children with disabilities.